Pooled Serum in House sebagai Bahan Kontrol untuk Pemantapan Mutu Internal - Nuraeni, Hanny Siti; Armal, Hadits Lissentiya; Astriani, Ranti Dwi (Politeknik Kesehatan Kementerian Kesehatan Banten, 2025)
One method used to carry out internal quality control at the analytical stage is to use control serum. . For some clinical laboratories, especially primary clinical laboratories where the number of clinical examinations is still small, the use of commercial control serum for quality control is not affordable because the cost is very expensive. Production of control materials from pooled blood serum can be used as an alternative to expensive production controls. The aim of this study was to find out whether serum collected at home can be used as a control material to carry out quality tests by determining its homogeneity and stability.The implementation process includes taking samples, sample from 48 person and then making pooled serum, examining pooled serum, homogeneity and stability tests, determining reference value ranges, and analyzing results. The combined serum that has been made is homogeneous and stable in the parameters of glucose and total cholesterol, while it is unstable in uric acid. The pooled serum value range for glucose is 49-86 mg/dL, total cholesterol 196-288 mg/dL and uric acid 1.36-3.70 mg/dL. The results of making pooled serum as a control material are declared homogeneous and stable in terms of glucose and total cholesterol parameters so that it can be used as quality control in daily activities. Suggestions for future researchers to add other parameters related to clinical chemistry examinations.